Exploring cognitive, behavioral and autistic trait network topology in very preterm and term-born children - Leoni, Marguerite; Vanes, Lucy D.; Hadaya, Laila; Kanel, Dana; Dazzan, Paola; Simonoff, Emily; Counsell, Serena J.; Happé, Francesca; Edwards, A. David; Nosarti, Chiara (Frontiers in Psychology, 2023)
Introduction Compared to full-term (FT) born peers, children who were born very preterm (VPT; <32 weeks’ gestation) are likely to display more cognitive and behavioral difficulties, including inattention, anxiety and socio-communication problems. In the published literature, such difficulties tend to be studied independently, thus failing to account for how different aspects of child development interact. The current study aimed to investigate children’s cognitive and behavioral outcomes as interconnected, dynamically related facets of development that influence one another. Methods Participants were 93 VPT and 55 FT children (median age 8.79 years). IQ was evaluated with the Wechsler Intelligence Scale for Children—4th edition (WISC-IV), autism spectrum condition (ASC) traits with the social responsiveness scale—2nd edition (SRS-2), behavioral and emotional problems with the strengths and difficulties questionnaire (SDQ), temperament with the temperament in middle childhood questionnaire (TMCQ) and executive function with the behavior rating inventory of executive functioning (BRIEF-2). Outcome measures were studied in VPT and FT children using Network Analysis, a method that graphically represents partial correlations between variables and yields information on each variable’s propensity to form a bridge between other variables. Results VPT and FT children exhibited marked topological differences. Bridges (i.e., the variables most connected to others) in the VPT group network were: conduct problems and difficulties with organizing and ordering their environment. In the FT group network, the most important bridges were: difficulties with initiating a task or activity and prosocial behaviors, and greater emotional problems, such as lower mood. Discussion These findings highlight the importance of targeting different aspects of development to support VPT and FT children in person-based interventions.